Serum sex steroid hormones and frailty in older American men of the Third National Health and Nutrition Examination Survey (NHANES III) - Eichholzer, Monika (Aging Male, 2012)
OBJECTIVE: To determine whether frailty is associated with circulating total and free testosterone, total and free estradiol, and sex-hormone binding globulin (SHBG) in older men. METHODS: With NHANES III data of 461 men aged 60 years and older, we used logistic regression to analyze the associations between serum concentrations of sex steroid hormones, SHBG and frailty. Participants meeting any 3 or more of the 5 frailty criteria were classified as “frail”, all others were considered as non-frail. RESULTS: 2.5% of men were frail. Men with SHBG ≥66 nmol/L had three times the odds of frailty (OR=2.97; 95% CI 1.28–6.86) compared to men with SHBG <66 nmol/L. Men with free testosterone levels below 243 pmol/L had an increased odds of frailty (OR=3.92; 95% CI 1.29–11.89). None of these associations was statistically significant after additionally adjusting for body mass index, smoking and history of cardiovascular diseases (CVD). Total testosterone, and total and free estradiol serum levels were not statistically significantly associated with frailty. CONCLUSIONS: In this US nationally representative study of older men, low free testosterone and high SHBG serum levels were associated with a significantly increased odds of frailty after adjustment for age and race/ethnicity. These associations may, however, be explained by confounding due to obesity, smoking, and the higher prevalence of cardiovascular disease in frail men or by low hormones or high SHBG mediating the association between obesity, smoking, CVD and frailty.